Tricksters, Travelers, and Other Places in Gloria Naylor’s Mama Day and Paule Marshall’s The Chosen Place, The Timeless People (Papers in Arts and Humanities, 2025)
This article explores the narrative representations of traveling, crossing, and identity formation in Gloria Naylor’s Mama Day and Paule Marshall’s The Chosen Place, The Timeless People. Informed by Henry Louis Gates’ analysis of the trickster archetype, the article casts a closer look at the role played by this symbolic figure in the two novels. Significant rites of passage require significant places, such as the “other place” in Mama Day or the “chosen place” in The Chosen Place, The Timeless People, which are the realm of the trickster. Deeply anchored in their island communities, these characters easily move between the supernatural and the mundane and facilitate access to cultural memory and personal identity. By juxtaposing these two works, the article argues that rites of passage, performed by bridge-like characters in culturally significant places, are essential for validating the characters’ inner and spatial journeys, ultimately assisting them in finding a sense of collective belonging and personal identity.
Keywords: Black diaspora; trickster; traveler; rites of passage; identity